2009
DOI: 10.1016/j.tvjl.2008.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of rapid assays for the detection of bovine coronavirus, rotavirus A and Cryptosporidium parvum in faecal samples of calves

Abstract: Rapid immunochromatographic assays for detecting infections with bovine coronavirus (BCV), rotavirus A and Cryptosporidium parvum in calf faeces were evaluated using as gold standards a reverse transcriptase polymerase chain reaction (BCV and rotavirus) and a sedimentation-flotation technique (C. parvum). Rapid tests for the detection of BCV and rotavirus showed a high specificity (96.4% and 95.3%, respectively), but a relatively low sensitivity (60.0% and 71.9%, respectively). Sensitivity and specificity for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 7 publications
3
36
2
1
Order By: Relevance
“…For these tests to provide benefit to livestock producers, it is important that users appreciate each test's limitations. 38 The coronavirus assay in that study showed a greater sensitivity (60%), specificity (96.4%), positive (91.3%) and negative predictive values (79.1%) than the coronavirus LAT assay examined in our study. The rotavirus assay in that study also showed a greater sensitivity (71.9%), specificity (95.3%) and negative predictive value (94%), but a lower positive predictive value (76.7%) than the rotavirus LAT assay in our study.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…For these tests to provide benefit to livestock producers, it is important that users appreciate each test's limitations. 38 The coronavirus assay in that study showed a greater sensitivity (60%), specificity (96.4%), positive (91.3%) and negative predictive values (79.1%) than the coronavirus LAT assay examined in our study. The rotavirus assay in that study also showed a greater sensitivity (71.9%), specificity (95.3%) and negative predictive value (94%), but a lower positive predictive value (76.7%) than the rotavirus LAT assay in our study.…”
Section: Discussioncontrasting
confidence: 49%
“…A previous study comparing the detection of rotavirus using LAT found a sensitivity and specificity of 70% and 100%, respectively, when compared with electron microscopy of 74 faecal samples from calves with acute diarrhoea. 6 Luginbühl et al 39 also found that the same rotavirus dipstick as that studied by Klein et al 38 had much lower sensitivity (57%), but the specificity was greater (100%) when compared with an ELISA for the detection of antigens in the faeces of 60 calves. Possible reasons for the difference in our results are that the sample size was much greater in our study and a more sensitive technology was used as the reference assay.…”
Section: Discussionmentioning
confidence: 91%
“…This diagnostic kit has been designed and approved for the diagnosis of animal RVAs, and has shown 72% sensitivity and 95% specificity to detect bovine RVA in calves (Klein et al, 2009). In the present study, the assay was able to detect both genotypes (G3P[12]I6 and G14P[12]I2) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several approaches have been developed for this purpose, including enzyme immunosorbent assays (EIAs), immune chromatography tests, latex agglutination, dot hybridization, polyacrilamide gel electrophoresis, RT-PCR, and direct and immune electron microscopy assays (Brooks et al, 1989;Cicek et al, 2007;Cornaglia et al, 1989;Cho et al, 2012;Dennehy et al, 1988Dennehy et al, , 1999Dennehy et al, , 1994Eing et al, 2001;Klein et al, 2009;Lipson et al, 2001;Maes et al, 2003;Marchlewicz et al, 1988). Apart from a few exceptions, the diagnostic methods that are commercially available are mainly designed to detect human RVA strains.…”
Section: Introductionmentioning
confidence: 99%
“…The sporulated oocysts spread by the faeces which has long survival capacity with high resistence to environmental conditions and this is the form frequently used in the diagnosis in practice [6] . Studies comparing the diagnostic methods for Cryptosporidium parvum in calf faeces revealed high sensitivity and specificity for the rapid tests [8] .…”
Section: Introductionmentioning
confidence: 99%